Membangun Generasi Muda, Kreatif dan Mandiri : Edukasi Kewirausahaan di SMP PAB 23 Bandar Klippa - Rindu Kinanti; Rasta Kurniawati Br. Pinem (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This study aims to describe the entrepreneurship education process at SMP PAB 23 Bandar Klippa as a strategic step in developing a creative and independent young generation. The approach used is descriptive qualitative with data collection techniques through observation and interviews with one principal, three teachers, and thirty-nine students. The research activities were carried out during the Real Work Lecture (KKN) program which lasted for ten days in September 2025. The main focus of the study was the Market Day activity designed as a learning tool for entrepreneurial practices in the school environment. The results showed that this activity was able to foster an entrepreneurial mindset, increase creativity, build collaborative skills, and foster students' confidence in planning and managing simple businesses. Thus, entrepreneurship education has been proven to play an important role in fostering independence, creativity, and readiness of students to face future economic challenges.